New vision 2050 : a platinum society - Komiyama, Hiroshi; Yamada, Koichi (Science for Sustainable Societies, 2018)
Sustainability; Climate change; Saturation; Leading country in resolving societal problems; Resource self-sufficiency; Urban mines; Renewable energy; Human-nature symbiosis; Aging society; Longevity; Lifelong learning; Sustainable cities; Low carbon society; Zero emission; Quality of life